2018
DOI: 10.1007/s00464-018-6332-8
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of 3D printed superior mesenteric vascular models for surgical planning and/or navigation in right colectomy with extended D3 mesenterectomy: comparison of virtual and physical models to the anatomy found at surgery

Abstract: This study showed acceptable dimensional inter-arterial correlations between 3D printed models, 3D virtual models and authentic soft tissue anatomy of the central mesenteric vessels, and weaker inter-venous correlations between all the models, reflecting the highly variable nature of veins in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…Luzon et al . used 3D printing to evaluate the linear dimensional differences in the anatomical landmarks of the superior mesenteric artery and vein among 3D virtual models, 3D printed models and preoperative measurements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Luzon et al . used 3D printing to evaluate the linear dimensional differences in the anatomical landmarks of the superior mesenteric artery and vein among 3D virtual models, 3D printed models and preoperative measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [8][9][10][11][12][13][14][15][16] were found to be eligible for the present review, all of which were included. The studies were published between 2014 and 2018.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with rapid technological advances, surgeons must play a more active role in the assessment and implementation of new navigation systems and ensure that such innovations will meet the surgeon's (and the patient's) needs. This also entails the role to assess various 3D anatomical format, physical or virtual, which are the main ingredients of any surgical navigation system [45].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment strategies vary considerably according to anatomic location, staging, among other factors [64]. 3D printed anatomic models have shown some utility in delineating relevant surgical anatomy for resection of colorectal cancer [45,46].…”
Section: Gastrointestinalmentioning
confidence: 99%